Pengembangan dan Peningkatan Volume UMKM Sapu Lidi Khususnya Ekonomi untuk Budaya Kesejahteraan Masyarakat dengan Mengelola Sumber Daya Lokal Desa Perkebunan Maryke - Dedek Ardiansyah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
The source of income in the region is the main capital for local residents to meet their living needs as social beings who have basic human nature in increasing social interaction. This is one of the reasons why humans form groups or communities. This community service activity was carried out in order to increase environmental knowledge and observe the main problems in a village, namely Maryke Plantation Village, Langkat Regency, Kutambaru District. The method used in this community service is face-to-face (on the spot training). Data collection is carried out through observation, interviews, and documentation. The result of this community service is in the form of efforts to invite residents to be careful of online lending and illegal collection on behalf of village officials. In addition, this activity also aims to provide education on ways to protect yourself from fraud and increase awareness of rights